Allweather Training - beating the elements - Whitehead, C.; Harrison, A.; McConnell, A.; Whyte, G.; Hamilton, A.; Maughan, R. (Peak Performance, 2005)
Peak athletic performance is not just about getting the most out of your body; it is also about anticipating and meeting the various challenges thrown at you by different environmental conditions, including hot and cold climates, altitudinous terrain and polluted cities. And it is about preparing yourself to be at your best at different times of the day and in far-flung time zones. Starting with a comprehensive pre-competition strategy for staying cool in the heat, move on to consider the various techniques for pre-cooling (useful in winter as well as summer!), then go on to look at the impact of pollution on performance. Next, altitude training: does it really aid sea-level performance or is it a rather expensive waste of time? On to the problems of working out in the cold - and you might be surprised to learn that dehydration can be as much - if not more - of a problem in freezing conditions than in the heat. Which brings us neatly to our final two articles on the core issue of fluid balance, the first weighing up the pros and cons of sports drinks as compared with plain water, and the second helping you to calculate your individual fluid needs (yes, they really do vary widely) and devise your personal hydration plan.